The Role of Code-Mixing in TikTok Content: How Mixed Language Videos Affect Students’ Vocabulary Growth at SMAN 1 SOJOL - Fina Nurdiana; Muhammad Arid; Wahyudin Wahyudin; Mochtar Marhum (MASI Mandiri Edukasi, 2026)
The widespread use of TikTok among students has increased their exposure to English–Indonesian code-mixing, which may influence vocabulary learning. However, empirical evidence regarding the effect of code-mixed TikTok content on students’ vocabulary development remains limited. Therefore, this study aims to investigate the effect of TikTok content containing English–Indonesian code-mixing on students’ vocabulary development at SMAN 1 Sojol. This study employed a quantitative pre-experimental design with a one-group pre-test and post-test. The participants were 27 students from class X-C, selected through purposive sampling. Vocabulary tests and classroom observations were used as research instruments, and the data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test. The results showed a significant improvement in students’ vocabulary mastery, with the mean score increasing from 57.78 in the pre-test to 74.63 in the post-test, resulting in an average gain of 16.85 points. The statistical analysis revealed a p-value of 0.000 (< 0.05), indicating a significant effect of the treatment. These findings suggest that exposure to code-mixed TikTok content effectively enhances students’ vocabulary acquisition by providing contextual, engaging, and multimodal language input. Thus, TikTok can be considered an effective supplementary learning tool to support English vocabulary development.